Anatomical insights beyond the centre edge angle in borderline hip dysplasia: A computerised tomography study - Joaquín Lara; Alejandro Neira; Alan Garín; Javier delRío; Alexander Tomic; Nicolás García; Matías Roby; Carlos De la Fuente PhD (Journal of Experimental Orthopaedics)
Abstract Purpose Borderline hip dysplasia (BhD) may be associated with insufficient acetabular coverage. Thus, we investigated potential differences in acetabular anatomical measurements derived from computerised tomography (CT) that characterise BhD compared with healthy controls. Methods BhD patients (lateral centre edge angle [LCEA] between 18° and 25°) and healthy controls (LCEA between 25° and 40°) underwent anteroposterior pelvic X‐ray and CT scans to study the Wiberg and Tönnis angle, the extrusion and Fear indices, notch width and depth, anterior and posterior wall heights, anterior and posterior articular surfaces, articular circumference, the ratio between the anterior articular surface and the articular circumference, the ratio between the posterior articular surface and the articular circumference, and the ratio between the notch width and the articular circumference. Independent two‐tailed t‐tests, Mann–Whitney U tests, and odds ratios were obtained (α = 5%). Results Twenty‐three BhD patients (aged 31.5 ± 8.3 years and LCEA 21.6° ± 4.0°) and thirty‐one healthy controls (aged 34.1 ± 8.0 years and LCEA 33.7° ± 5.5°) were included. The CT features most sensitive for detecting BhD were the anterior acetabular surface (p < 0.001) and ratios of anterior (p = 0.009), anteroposterior (p = 0.008) and posterior (p < 0.008) acetabular surfaces, as well as acetabular notch width (p = 0.002). Conclusions CT characterisation showed insufficient acetabular coverage in BhD patients along the superior axis (lower Wiberg angle, and increased Tönnis angle and extrusion index), anterior axis (lower anterior acetabular surface and anteroposterior acetabular surface ratio, and increased posterior acetabular ratio), and inferior axis (increased acetabular notch width). These structural alterations suggest that periacetabular osteotomy may address persistent pathological deformation and stress on soft tissues and cartilage‐bone structures more effectively. Level of Evidence Diagnostic III.